Malevolent Forces: Self-Control, the Dark Triad, and Crime - Wright, John Paul (Youth violence and juvenile justice, 2017)
The Dark Triad is represented by three interrelated personality characteristics thought to share a “dark core”—that is, to be associated with a range of negative outcomes. We investigate this link alongside another potent predictor of crime, low self-control. Our analyses found the Dark Triad was strongly predictive of delinquency, especially violent delinquency, where it accounted for the effects of self-control. Yet it exerted no significant effect on drug-based delinquency. However, an interaction between the Dark Triad and low self-control remained substantive and predictive across all models, where low self-control amplified the effects of the Dark Triad on delinquency.